Exploration of the protective mechanisms of Icariin against cisplatin-induced renal cell damage in canines - Liu, Jiayi; Xie, Liuwei; Zhai, He; Wang, Dongwei; Li, Xiao; Wang, Yao; Song, Mingqiang; Xu, Chao (Frontiers in Veterinary Science, 2024)
This study delves into the protective mechanisms of Icariin (ICA) against cisplatin-induced damage in madin-darby canine kidney (MDCK) cells. Comprising two distinct phases, the investigation initially employed a single-factor randomized design to ascertain the minimal cisplatin concentration eliciting MDCK cell damage, spanning concentrations from 0 to 16 mmol/L. Concurrently, various concentrations of ICA (ranging from 5 to 50 mmol/L) were combined with 1 mmol/L cisplatin to determine the most efficacious treatment concentration. Subsequent investigations utilized four treatment groups: control, 1 mmol/L cisplatin, 1 mmol/L cisplatin + 20 mmol/L ICA, and 1 mmol/L cisplatin + 25 mmol/L ICA, aimed at elucidating ICA's protective mechanisms. Findings from the initial phase underscored a significant reduction in MDCK cell viability with 1 mmol/L cisplatin in comparison to the control (P<0.01). Notably, the inclusion of 20 and 25 mmol/L ICA substantively ameliorated MDCK cell viability under 1 mmol/L cisplatin (P<0.01). Moreover, cisplatin administration induced an elevation in inflammatory factors, malondialdehyde (MDA), reactive oxygen species (ROS), and Bax protein levels, while concurrently suppressing superoxide dismutase (SOD), catalase (CAT), and Bcl-2 expression (P<0.01). Conversely, supplementation of 20 and 25 mmol/L ICA demonstrated a marked increase in mitochondrial membrane potential and levels of SOD, CAT, and Bcl-2 (P<0.01). These interventions effectively attenuated inflammatory responses and suppressed Bax protein expression (P<0.05), consequently mitigating cisplatin-induced apoptosis in MDCK cells (P<0.01). In summary, these findings elucidate the role of ICA in impeding apoptosis in cisplatin-induced MDCK cells by regulating inflammatory responses, oxidative stress, and autophagic protein expression.